2015
DOI: 10.1039/c5ra17186e
|View full text |Cite
|
Sign up to set email alerts
|

Dual functionalized task specific ionic liquid promoted in situ generation of palladium nanoparticles in water: synergic catalytic system for Suzuki–Miyaura cross coupling

Abstract: A new task specific ionic liquid with hydroxyl and prolinate functionalities acts as a reducing agent and serves as a ligand and stabilizer for in situ formed palladium nanoparticles. This system displays high catalytic activity for Suzuki–Miyaura cross-coupling in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 128 publications
0
6
0
Order By: Relevance
“…In spite of abundant reports on performing the Suzuki-Miyaura coupling reactions, developments to improve it are currently done. For example, conducting the Suzuki-Miyaura coupling reaction in environmentally friendly solvents such as water have particular importance [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Water is a great alternative to organic solvents which disposal is a main problem in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of abundant reports on performing the Suzuki-Miyaura coupling reactions, developments to improve it are currently done. For example, conducting the Suzuki-Miyaura coupling reaction in environmentally friendly solvents such as water have particular importance [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Water is a great alternative to organic solvents which disposal is a main problem in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, developing new catalysts for the synthesis of 3acylindoles with excellent yields and high selectivity under mild and environmentally friendly conditions is highly desirable. 18 Ionic liquids have received much attention in many elds including catalysis, [19][20][21][22][23][24][25] electrolytes, [26][27][28][29] extraction desulfurization, [30][31][32] biomass processing, [33][34][35] and biodiesel. [36][37][38][39] Friedel-Cras C3-acylation of indoles using ionic liquids has been reported in previous literature.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to many of the mentioned catalysts, supported catalysts used in SuzukiMiyaura cross-coupling reaction with good coordination ability, easy synthesis, cost-effectiveness, and high thermal stability have become the core research focus of scientic researchers. [20][21][22][23][24][25] A number of studies have been reported for the immobilization of palladium nanocatalysts on support materials such as polyvinyl pyrrolidone 26 (PVP), amphiphilic resin,…”
Section: Introductionmentioning
confidence: 99%